Faktor Risiko pada Peningkatan Kasus Multidrug-Resistant Tuberculosis (MDR-TB) di Indonesia: Tinjauan Literatur - Chandra, Benny; Fikriana, Riza; Nurbadriyah, Wiwit Dwi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Objective: to analyze the risk factors that affect MDR-TB in Indonesia through a literature review. Methods: This study employed a literature review method to analyze the risk factors contributing to the increase in multidrug-resistant tuberculosis (MDR-TB) cases in Indonesia. Relevant articles published between 2020 and 2024 were selected through databases such as Google Scholar, Garuda Kemdikbud, and ResearchGate, with the final analysis focusing on 9 articles that met the inclusion criteria. Results: The results of the study showed that the incidence of MDR-TB was influenced by internal factors such as TB treatment history, drug availability, nutritional status, comorbidities (diabetes, HIV/AIDS), drug side effects, and smoking. External factors include housing density, social support, socioeconomic conditions, access to health facilities, the role of PMOs, history of contact with MDR-TB patients, and jobs that increase risk. Conclusion: The practical implications are the importance of improving the implementation of treatment through DOT and technology programs, patient education, and management of risk factors such as smoking, malnutrition, and comorbidities. Improving access to health, social support, and healthier environmental conditions can also prevent the spread and improve the success of MDR-TB treatment.